PELATIHAN TOEFL UNTUK SISWA/SISWI KELAS UNGGUL DI SMA NEGERI 8 KOTA BENGKULU - Ivan Achmad Nurcholis; Maryansyah, Yupika; Suhadi, Agung (TRIMAS: Jurnal Inovasi dan Pengabdian Kepada Masyarakat, 2023)
This training was conducted to provide understanding and knowledge to students of superior class XII IPA 1 and superior class XII Social 1 about TOEFL because many of them did not know what TOEFL was, what was the importance of TOEFL, what are the forms of TOEFL, and what were the strategies for answering TOEFL questions correctly. The methods used in this training were lectures, discussions, exercises, and discussions. All costs for implementing PkM activities came from the PkM implementing team personnel. The results of the activity show that students have knowledge and understanding related to TOEFL test questions and TOEFL skills material. This is due to the training methods of the instructors and positive responses from students. It is suggested that this activity can be continued regularly in the future.